Synergistic electronic coupling/cross-talk between the isolated metal halide units of zero dimensional heterometallic (Sb, Mn) halide hybrid with enhanced emission. Issue 1 (13th December 2021) - Biswas, Anupam; Bakthavatsalam, Rangarajan; Das, Deep K.; Sam, Jisvin; Mali, Bhupendra P.; Biswas, Chinmoy; Maana, Narugopal; Thomson, Stuart; Raavi, Sai Santosh Kumar; Kurungot, Sreekumar; Gonnade, Rajesh G.; Dutta, Sudipta; et al.
Abstract : Reported here is a heterometallic 0D hybrid with constituent isolated metal halide units (Sb, Mn) that show strong synergistic interaction/coupling between the metal halide units (through Sb → Mn energy transfer) that results in enhanced emission. Abstract : Heterometallic 0D metal halide hybrids, consisting of more than one kind of metal halide units, are anticipated to manifest synergistic effects on the photo-physical properties of the constituent metal halide units. Such architectures hold great promise for design and development of function-targeted materials. However, heterometallic 0D hybrids, featuring isolated metal halide units, typically do not show any synergistic effects due to large inter-unit spatial separations that inhibit interactions/coupling between the constituent metal halide units. It remains challenging to design synthetic strategies that would support structural modifications to allow synergistic electronic coupling between the metal halide units in heterometallic 0D hybrids. Here, we report synthesis and characterization of heterometallic (Sb, Mn) 0D hybrid, namely Tris SbMnCl, with isolated MnCl5 units, (Sb/Mn)Cl6 units, dispersed in the organic ligand matrix and layer of dynamic and networked water molecules. Steady state and time resolved emission spectra (TRES) analysis suggests strong synergistic interaction between the isolated metal halide units. Efficient energy transfer from the strongly absorbing Sb centres to emissive Mn centres results in the observed enhanced emission. Proton conductivity measurements together with first-principles calculations suggest the unique role of the networked water molecules in mediating the electronic coupling/energy transfer between the separated metal halide units in Tris SbMnCl hybrid. This report highlights the role of structure/composition of the synthesized heterometallic 0D hybrid in attaining electronic dimensionality higher than 0D through synergistic electronic interaction between the isolated metal halide units.